De novo donor-specific HLA antibody development after kidney transplantation is impacted by PIRCHE II score and recipient age - Tian, Yuan; Frischknecht, Lukas; Rössler, Fabian; Schachtner, Thomas; Nilsson, Jakob (Frontiers in Immunology, 2025)
BackgroundAntibody-mediated rejection (ABMR) is a major cause of graft loss in kidney transplantation, often associated with de novo donor-specific antibodies (dnDSA). The detection of clinically relevant dnDSA relies on evaluating reactivity in single antigen bead (SAB) assays. Immunogenetic mismatches between donor and recipient, particularly involving human leukocyte antigens (HLA), underpin dnDSA development. Understanding this relationship could improve pre-transplant risk assessment and organ allocation.MethodsWe analyzed 1296 kidney transplant patients to study dnDSA development, its relation to age, gender, and the role of HLA-derived peptide mismatches using the Predicted Indirectly Recognizable HLA Epitopes II (PIRCHE II) score. We categorized dnDSA based on bead reactivity patterns and HLA typing into true, possible, and false dnDSA.ResultsDuring follow-up, 25% of recipients developed dnDSA, 9.3% true, 7.7% possible, and 7.9% false. True dnDSA primarily targeted HLA-DQ (38%), while HLA-C and HLA-DP were uncommon (5% and 3%). Higher PIRCHE II scores were significantly associated with true and possible dnDSA against HLA Class II compared to false dnDSA, supporting our dnDSA classification. For true and possible dnDSA, the single locus PIRCHE II score strongly correlated with locus-specific dnDSA, while the total PIRCHE II score did not appear to influence locus-specific dnDSA development. Younger recipients exhibited a higher risk of dnDSA development, while gender had no impact.ConclusionLocus-specific PIRCHE II scores are useful in predicting dnDSA risk post-transplantation, particularly in younger recipients. Promoting transplants with low PIRCHE II scores against key HLA loci like HLA-DQ in younger recipients could improve outcomes.